(untitled) (Altre Modernità, 2015)
Diego Enrique Osorno, Un vaquero cruza la fontera en silencio. La historia de Gerónimo González Garza (Ciudad de México, CONAPRED, 2011, 123 pp.) por Ana María González Luna C.